Application of Lumio By SMART Media in Increasing Student Learning Independence in Islamic Religious Education Subjects - Siti Khodijah; Nurul Wahdah; Muhammad Redha Anshari (Didaktika: Jurnal Kependidikan, 2024)
This research aims to increase student learning independence in PAI students by implementing Lumio By SMART media. This research uses PTK (classroom action research) with the stages of planning, acting, observing and reflecting. The research subjects were 30 students of class in learning PAI (Islamic Religious Education). The instruments used in the research were observation sheets, questionnaires. Based on research results, it proves that Lumio by SMART media is able to increase student learning independence. This can be seen from the increase in student learning independence in PAI learning using Lumio by SMART media, namely in cycle I 66.4% with details: Very Independent = 8.1%, Independent = 10%, Less independent = 13.1%, Not Independent=15.2%, very not independent=20%. From cycle I there was a change to cycle II to 90% with details: Very Independent = 70%, Independent = 15%, Less independent = 5%, Not Independent = 0%, very not independent = 0%, with the percentage value of student learning independence increased to 72.60%, meaning there has been a significant increase.